Kajian Teknis Penanganan Lumpur Untuk Optimalisasi Chemical Injection Pada Kpl 13 Di Pt Powerindo Kimia Mineral Lahat Sumatera Selatan - Akhramdani, Akhramdani; Arisanti, Reni; Husni , Ahmad (Riviera Publishing, 2025)
Acid mine drainage management and sludge settling efficiency at KPL 13 play an important role in ensuring the quality of wastewater before it is discharged into the environment to meet the quality standards set by the government. The study was conducted using field observation methods, primary data collection (TSS, water discharge, pond dimensions), and secondary data (rainfall, company data). The results showed that before maintenance, KPL 13 experienced a decrease in settling efficiency due to full pond conditions and landslides, so that the TSS at the outlet remained high. After maintenance, the sludge settling efficiency increased significantly, indicated by a decrease in the TSS value at the outlet. The addition of chemical injections such as Powerbase 3028, Powerclear 1228, and Powerfloc 4888 succeeded in reducing TSS levels effectively in each compartment. This study provides recommendations regarding the frequency of pond maintenance and improvements to compartment design to maximize sludge settling capacity. The results of this study obtained a TSS reduction value of 20-30 Mg/L after maintenance, which means that the TSS reduction was successful and improved the performance of the sludge settling pond.